2015
DOI: 10.1160/th14-04-0335
|View full text |Cite
|
Sign up to set email alerts
|

Red cell distribution width is associated with incident venous thromboembolism (VTE) and case-fatality after VTE in a general population

Abstract: Recent studies suggest an association between red cell distribution width (RDW) and incident venous thromboembolism (VTE). We aimed to investigate the impact of RDW on risk of incident and recurrent VTE, and case-fatality, in a general population. RDW was measured in 26,223 participants enrolled in the Tromsø Study in 1994-1995. Incident and recurrent VTE events and deaths during follow-up were registered until January 1, 2012. Multivariate Cox proportional hazards regression models were used to calculate haza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 40 publications
5
17
0
Order By: Relevance
“…Our results suggest that high body iron stores may increase the risk of VTE. In agreement with previous studies, 16,17 we demonstrated a doseresponse relationship between RDW and risk of VTE. Adjusting for hepcidin and FtL increased rather than reduced the risk estimates for VTE by RDW, suggesting that these parameters may, at least partly, reflect different pathways in VTE development.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results suggest that high body iron stores may increase the risk of VTE. In agreement with previous studies, 16,17 we demonstrated a doseresponse relationship between RDW and risk of VTE. Adjusting for hepcidin and FtL increased rather than reduced the risk estimates for VTE by RDW, suggesting that these parameters may, at least partly, reflect different pathways in VTE development.…”
Section: Discussionsupporting
confidence: 93%
“…Red cell distribution width (RDW) has in recent years been associated with several diseases, 14 including VTE, [15][16][17] but the underlying mechanisms remain unknown. RDW is traditionally used in a classification system for anemia, 18 and iron deficiency anemia is strongly associated with high RDW.…”
Section: Introductionmentioning
confidence: 99%
“…The baseline RDW and increase in RDW during hospitalization are also compared in patients with sepsis and heart failure (16,17). It is reported that there is an increase in RDW from baseline during the first 72 hours after hospitalization and it is significantly associated with adverse clinical outcomes in sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that there is an increase in RDW from baseline during the first 72 hours after hospitalization and it is significantly associated with adverse clinical outcomes in sepsis. Therefore, it is suggested that a combination of baseline RDW value and an increase in RDW can be a promising independent prognostic marker in patients with severe sepsis or septic shock (17). It is also suggested that both initial RDW and change of RDW during hospitalization may be helpful in personalizing prognosis and treatment in patients with heart failure (16).…”
Section: Discussionmentioning
confidence: 99%
“…Uhm et al [30] from Korea performed to compare clinical and imaging parameters and prognosis of provoked and unprovoked acute PE patients and they found that provoked PE with irreversible risk factors has a poor prognosis for all-cause mortality and recurrent PE than unprovoked PE and provoked PE with reversible risk factors. Ellingsen et al [31] suggested that high RDW is a risk factor of incident VTE, and that RDW is a predictor of all-cause mortality in VTE patients. All of these studies show that VTE treatment needs to be rearranged according to associated risk factors.…”
Section: Discussionmentioning
confidence: 99%